Study of Effectiveness of a Social-Economic Intervention for Sexual Violence Survivors in Eastern DRC - Bass, Judith; Bolton, Paul; Murray, Sarah; Cole, Gabrielle; Robinette, Katie; Poulton, Catherine; Murfet, Tamah; Bakayoko-Topolska, Monika; Greco, Daniela; Wachter, Karin; Cetinoglu, Dalita; Annan, Jeannie (World Bank, Washington, DC, 2017)
Violence against women is increasingly being recognized as an urgent public health priority and a significant human rights concern, as well as a major threat to social and economic development. Globally, an estimated 20 percent of all women will face some form of violence during their lifetime, including emotional coercion, physical violence, and sexual violence. The overall objective of the impact evaluation is to identify low-cost and scalable interventions, which demonstrate improvements in social, psychological, and economic functioning of sexual violence survivors in eastern Democratic Republic of Congo (DRC). To this end, the authors conducted an impact evaluation of a village savings and loans association (VSLA) program to understand its impact on economic, social, and psychological outcomes for a sample of female sexual violence survivors. The impact evaluation had four components: (1) a qualitative needs assessment; (2) a quantitative baseline assessment; (3) a qualitative post-program assessment; and (4) a quantitative post-program assessment. This report presents a brief description of components 1 and 2 and then a full description of the method and results of the impact evaluation focusing on components 3 and 4. In terms of improving the psychological, social, and economic well-being of survivors of sexual violence, this study shows important results in some of the social and economic outcomes, but fewer results than expected for psychological outcomes. One recommendation from these results will be to explore the idea of pairing VSLA with other interventions to work more specifically on the certain outcomes that VSLA may not change on its own.